High throughput sequencing sheds light on the viral diversity in Aedes aegypti mosquitoes from Binh Thuan Province, Vietnam. - Margarita Popova; Anna Gladkikh; Alena Sharova; Tatiana Arbuzova; Valeriya Sbarzaglia; Ekaterina Klyuchnikova; Nadezhda Tsyganova; Majid Forghani; Anastasia Gritseva; Edward Ramsay; Nguyen Thanh Dong; Bui Thanh Phu; et al. (PLoS ONE)
Mosquitoes are important vectors for various infectious pathogens. More than 200 species of mosquitoes are common in Vietnam, one of the main carriers of viruses that are important for humans is the mosquito of the genus Aedes aegypti. Metavirome sequencing can shed light on the diversity of mosquito-borne viruses classified as insect-specific viruses (ISV). After BLAST analysis using the viral database, contigs were classified as belonging to seventeen ISVs. Ten of them are distributed among five families: Totiviridae; Flaviviridae; Partitiviridae; Phenuiviridae; and Orthomyxoviridae. The other seven species belonged to recently identified RNA viruses whose taxonomic position is undefined in the current classification of the International Committee on Taxonomy of Viruses (ICTV). This is the first study to reveal the diversity of RNA viruses associated with Aedes aegypti mosquitoes in Vietnam, while highlighting the need for further study of ISV in mosquito vectors.